Carbon Monoxide‐Releasing Molecule Enhances Coagulation and Decreases Fibrinolysis in Normal Canine Plasma. Issue 3 (6th May 2018) - Donaghy, Dillon; Yoo, Seung; Johnson, Tyler; Nielsen, Vance; Olver, Christine
Abstract: The dog is an important companion animal and also purpose‐bred for research studies. Coagulopathies in dogs are common, although the availability of blood products for therapy is inconsistent throughout the profession. A pro‐coagulant therapeutic that is readily available and easily stored would be useful for the treatment of coagulopathies. Tricarbonyldichlororuthenium (II) dimer [Carbon monoxide‐releasing molecule‐2 (CORM‐2)] acts as a prothrombotic agent in plasma by increasing the velocity of clot formation and clot strength, and by decreasing the clot's vulnerability to fibrinolysis. We sought to test CORM‐2's effect on coagulation and fibrinolysis in vitro in canine plasma using thromboelastography. Measures of the rate of clot formation and clot strength in plasma without CORM‐2 were highly correlated with fibrinogen concentration. We found that CORM‐2 significantly enhanced the rate of clot formation and clot strength and significantly reduced the rate of fibrinolysis and the clot lysis time. The per cent change in rate of clot formation and clot strength was not significantly correlated with fibrinogen concentration, indicating that CORM‐2's pro‐coagulant effect is not dependent on fibrinogen concentration. This study corroborates studies in other species that show that CORM‐2 is pro‐coagulant in plasma, and lays the groundwork for developing CORM‐2 as a therapeutic agent for canine coagulopathies. Future studies will evaluate the effect of CORM‐2 on whole blood both in vitro and in vivo .